Teachers Communication Strategies in Regulating Early Childhood Emotions - Firyal, Marzuqoh Nabilah; Maharani, Saffa; Muti’ah, Muti’ah; Zahra, Revalya Ananta; Azizah, Annafi Nurul Ilmi (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2026)
Purpose - This study aims to analyze teachers’ communication strategies in supporting young children's emotional regulation at RA Asmaul Husna Baki Sukoharjo and to identify contextual factors influencing the implementation of these strategies. Although emotional regulation has received considerable attention in early childhood education research, limited studies have specifically examined how teachers integrate verbal and nonverbal communication strategies within Islamic early childhood education settings. This study therefore addresses this gap by exploring teacher communication as the central mechanism for fostering children's emotional regulation. Design/methods/approach - A descriptive qualitative design was employed. Data were collected through in-depth interviews, participatory observations, and document analysis involving teachers and children aged 4–6 years at RA Asmaul Husna Baki Sukoharjo. Data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. Findings - Teachers implemented integrated verbal and nonverbal communication strategies to facilitate children's emotional regulation. Verbal communication included emotion labeling, conflict mediation, positive reinforcement, and reflective dialogue, while nonverbal communication involved facial expressions, voice intonation, gestures, physical proximity, and calming touch. These strategies encouraged children to recognize, express, and regulate their emotions more appropriately during classroom interactions. Research implications/limitations - The findings also reveal that the effectiveness of teacher communication was strongly influenced by the consistency of emotional support provided in the family environment, highlighting the importance of sustained collaboration between teachers and parents through structured parenting programs. Originality/value - This study contributes to the literature by proposing an integrated teacher communication framework that positions verbal and nonverbal communication as interconnected pedagogical practices for strengthening emotional regulation within the distinctive context of Islamic early childhood education.